Error estimate in the central limit theorem - Kasparavičiūtė, Aurelija; Padvelskis, Kazimieras (Lietuvos matematikos rinkinys, 2008)
In this paper, we determined, independent identically distributed random variable’s Xk, k = 1,2,... centered and normalized sum’s Sn = k=1 Xk distribution’s Fn(x) = P(Zn < x) exact error estimate in case of the normal approximation with one Cebyšova’s asymptotic expansion’s term.